The notch signalling regulator fringe acts in the Golgi apparatus and requires the glycosyltransferase signature motif DXD. - Munro, S; Freeman, M (2000)
BACKGROUND: Signalling via the Notch receptor is a key regulator of many developmental processes. The differential responsiveness of Notch-expressing cells to the ligands Delta and Serrate is controlled by Fringe, itself essential for normal patterning in Drosophila and vertebrates. The mechanism of Fringe action, however, is not known. The protein has an amino-terminal hydrophobic stretch resembling a cleaved signal peptide, which has led to the widespread assumption that it is a secreted signalling molecule. It also has distant homology to bacterial glycosyltransferases, although it is not clear if this reflects a shared enzymatic activity, or merely a related structure. RESULTS: We report that a functional epitope-tagged form of Drosophila Fringe was localised in the Golgi apparatus. When the putative signal peptide was replaced by a confirmed one, Fringe no longer accumulated in the Golgi, but was instead efficiently secreted. This change in localisation dramatically reduced its biological activity, implying that the wild-type protein normally acts inside the cell. We show that Fringe specifically binds the nucleoside diphosphate UDP, a feature of many glycosyltransferases. Furthermore, specific mutation of a DxD motif (in the single-letter amino acid code where x is any amino acid), a hallmark of most glycosyltransferases that use nucleoside diphosphate sugars, did not affect the Golgi localisation of the protein but completely eliminated in vivo activity. CONCLUSIONS: These results indicate that Fringe does not exert its effects outside of the cell, but rather acts in the Golgi apparatus, apparently as a glycosyltransferase. They suggest that alteration in receptor glycosylation can regulate the relative efficiency of different ligands.